The Relationship of Personal Factors and Family Support with Self-Management of Diabetes Mellitus Patients in Posbindu Working Area of Pisangan Puskesmas City of Tangerang Selatan - Jamaludin Jamaludin; Fatimah Fatimah; Uswatun Khasanah; Karyadi Karyadi (Budapest International Research and Critics University, 2022)
Based on data from the International Diabetes Federation in 2014 it was found that that increase in type 2 diabetes every year in every country and by 2035 it is estimated diabetes sufferers increase to 592 million people, and Indonesia is in 7th place. Diabetes is a disease degenerative that happened lifetime live. Diabetics will having hard times consequence changes in him, so that need endorsement from people around especially endorsement family for help him in dick pattern life and care management self families with diabetes. Diabetes is a disease chronic need management self diabetes for prevent serious complications. Study this aim for identify connection Among endorsement family with management self people with diabetes mellitus in Posbindu work area public health center South Tangerang City Banana. Design in study this use approach quantitative cross-sectional design with sample as many as 35 respondents. Data analysis using Chi Square test. Research results show that no there is connection Among endorsement family with management self diabetes with significance (p value = 0.274 at = 0.05). Researcher recommend the need deployment information related management self through counseling and also needed visit House for those who don't can present to posbindu because condition not physical possible, at once motivate family for help diabetics in control management self for prevent and avoid ongoing complications.